Persepsi Guru Kelas Pada Keterampilan Pembelajaran Abad Ke 21 Di SD Inpres 6/75 Ta Kecamatan Tanete Riattang Kabupaten Bone - Rahmawati Patta; Kiki Tri nanda Basri; abd kadir; asriadi asriadi (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a type of descriptive qualitative research that aims to find out how the perceptions of classroom teachers at SD Inpres 6/75 Ta Kecamatan Tanete Riattang Kabupaten Bone, regarding 21st century learning skills today. Data was collected by giving questionnaires (questionnaire) and in-depth interviews. Data reduction analysis techniques, data display, and conclusion drawing/verification. Class teachers' perceptions of 21st century learning can be viewed from four descriptors, namely, (1) Teacher's motivation to always apply 21st century skills. (2) Learning skills always support the components of creative thinking and collaboration of students. (3) Encouraging students to always demonstrate the ability to think critically and communicate well. (4) Teachers try to improve their quality by improving their information, media and technology skills. The results of the study showed that the 5 classroom teachers who were interviewed, 4 of whom did not experience obstacles in the implementation of 21st century learning, only 1 class teacher who experienced slight obstacles, namely during the ICT learning process where facilities and infrastructure were felt to be lacking to support the 21st century skills learning process. The conclusion of this study is that the perception of classroom teachers on 21st century learning at SD Inpres 6/75 Ta Kecamatan Tanete Riattang District Kabupaten Bone is said to be good and can improve students' skills in 21st century learning.